KUALITAS PELAYANAN NASABAH KREDIT BANK BNI CABANG PARIGI - Fatmawati, Fatmawati; Mustainah, Mustainah; Nawawi, Muhammad (Katalogis, 2019)
The purpose of this study is to determine the quality of services needed in lending at the BNI Bank Parigi Branch. The theory used in this study is a theory of service quality proposed by Zeithhaml in Hardiansyah (2011:46), which consists of Tangible, Reliabelity, Responsiviness, Assurance, danEmphaty. This research uses descriptive qualitative type, with the number of informants involved as many as 6 people with Purpossive techniques. Data collection techniques in this study through observation, interviews and documentation. With the data analysis method used in this study is an interactive data analysis model with steps: condensing data, presenting data, and drawing conclusions or verification. From the results of research that is known about the quality of loans provided by the approved BNI Bank Parigi Branch, this can be seen after going through the data analysis process related to the discussion made as a reference, there are still two that are not well implemented, second this aspect is responsiveness and assurance. While the other three aspects have been well implemented, namely: 1) Tangibles, where in the service the BNI Branch Office itself is supported by a variety of good facilities, such as waiting room facilities that are easy to open and cool and well organized, in service as well provided with service aids such as computers, internet networks, printers that are used for administrative purposes, even vehicles for motorbikes for marketing employees to directly by prospective buyers; 2) Reliability, where in carrying out its service duties, employees have been able to work well by minimizing problems in their services, all employees in this government can also use the tools in the service process quite well; 3) Guarantees are carried out properly, where in their services they prioritize the interests of service users. The Parigi Branch BNI Branch Office, this delay is related to completeness issues, incomplete loan application projects, and so on.The requested liquid funds; and 4) Empaty is well implemented because in its service, BNI Office employees in the Parigi Branch serve politely, build good relationships through services related to doing and polite speech in their services. Employees also serve by not being discriminatory or discriminating who they serve.